The air cooled condenser optimization - Squicciarini, Martin (Kansas State University, 2016)
Today air cooled chillers are often used in industrial applications where chilled water is pumped through processes or laboratory equipment. Industrial chillers are used for the controlled cooling of products, mechanisms and factory machinery in a wide range of industries. However, there is limited information on condenser coil design for a simulated model that uses R407c in a process chiller system with a focus on the finned tube condenser design. Therefore, a simulation tool that evaluates the performance of a condenser design, e.g. frontal area, cost, and overall system efficiency would be very useful. An optimization calculator for the air cooled fin-tube condenser design was developed. This calculator allows a user to specifically select the condenser geometric design parameters including the overall condenser length and height, number of rows, number of circuits, row and tube spacing, fin thickness, fin density, tube inner and outer diameters, and the quantity and power of the fan motors. This study applied the calculator finding an optimum condenser design for various frontal areas and cost constraints. The calculator developed is appropriate for engineering designers for use in the process chiller industry.
Keywords: Condenser; Condenser coil; HVAC; Calculator